2020
DOI: 10.7185/geochemlet.2003
|View full text |Cite
|
Sign up to set email alerts
|

Redox transfer at subduction zones: insights from Fe isotopes in the Mariana forearc

Abstract: Subduction zones are active sites of chemical exchange between the Earth's surface and deep interior and play a fundamental role in regulating planet habitability. However, the mechanisms by which redox sensitive elements (e.g., iron, carbon and sulfur) are cycled during subduction remains unclear. Here we use Fe stable isotopes (δ 56 Fe), which are sensitive to redox-related processes, to examine forearc serpentinite clasts recovered from deep sea drilling of mud volcanoes formed above the Mariana subduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 6 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…However, the lack of significant Fe isotope variation in the Cerro del Almirez samples is surprising as isotopically light Fe is also expected to be mobile in carbonate-bearing fluids (Fujii et al, 2014). Indeed, previous studies working in forearc mantle wedge or shallow slab/mantle interface areas have shown that large Fe isotope variations in ultramafic rocks (down to -0.26 ‰) may be attributed to carbonate-bearing metasomatism (Inglis et al, 2017;Debret et al, 2018bDebret et al, , 2020 and the dissolution of Ca-(i.e., calcites, aragonite) and/or Fe-(i.e., siderite and ankerite) bearing carbonates in metamorphic fluids at low temperature (i.e., below 400 °C; Facq et al, 2014;Milesi et al, 2015). Both Ca-(down to -0.92 ‰; Craddock and Dauphas, 2011) and Fe-(down to -3.9 ‰; Belshaw et al, 2000;Johnson et al, 2008) bearing seafloor carbonates are known to concentrate isotopically light Fe relative to silicate and oxide phases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the lack of significant Fe isotope variation in the Cerro del Almirez samples is surprising as isotopically light Fe is also expected to be mobile in carbonate-bearing fluids (Fujii et al, 2014). Indeed, previous studies working in forearc mantle wedge or shallow slab/mantle interface areas have shown that large Fe isotope variations in ultramafic rocks (down to -0.26 ‰) may be attributed to carbonate-bearing metasomatism (Inglis et al, 2017;Debret et al, 2018bDebret et al, , 2020 and the dissolution of Ca-(i.e., calcites, aragonite) and/or Fe-(i.e., siderite and ankerite) bearing carbonates in metamorphic fluids at low temperature (i.e., below 400 °C; Facq et al, 2014;Milesi et al, 2015). Both Ca-(down to -0.92 ‰; Craddock and Dauphas, 2011) and Fe-(down to -3.9 ‰; Belshaw et al, 2000;Johnson et al, 2008) bearing seafloor carbonates are known to concentrate isotopically light Fe relative to silicate and oxide phases.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the effects of seafloor alteration (e.g., serpentinization) on Fe and to a lesser extent on Zn isotope systematics of mantle peridotites are comparatively minor (Craddock et al, 2013;Debret et al, 2018a), such that subduction-related fractionation processes should be relatively straightforward to identify. Recent studies have successfully applied Fe and Zn stable isotopes in subduction settings to identify processes associated with high-pressure metamorphism in metabasites, meta-serpentinites and metasedimentary rocks (e.g., Debret et al, 2016;Pons et al, 2016;Inglis et al, 2017;El Korh et al, 2017;Debret et al, 2018b;Turner et al, 2018;Gerrits et al, 2019;Huang et al, 2019;Chen et al, 2019;Debret et al, 2020). In these studies, Fe and Zn stable isotopic variations were attributed to redox reactions and associated metal mobility in sulfur, carbon and chlorine-bearing fluids during metamorphic processes.…”
Section: Introductionmentioning
confidence: 99%
“…1A). Three types of serpentinized forearc peridotite clasts, namely, lizardite, antigorite, and blue serpentine-bearing clasts, were identified on the basis of their petrographic and geochemical features (35)(36)(37). These clasts record various stages of serpentinization from deep forearc mantle hydration by slab-derived fluids to shallow fluid-rock interaction during clast exhumation nearby the seafloor (Fig.…”
Section: Geological Setting and Sample Selectionmentioning
confidence: 99%
“…However, although this shallow fluid loss apparently strengthens the attribution of a high  56 Fe signature to serpentinite, it is likely not relevant for CLIPPIR diamonds. Fluid evolution in this process removes carbon, hindering later diamond growth, and produces variably oxidizing conditions (32,33) that would be difficult to reconcile with the reduced nature of the metallic inclusions studied here. Such shallow devolatilization typically affects hotter slabs, whereas CLIPPIR diamonds are thought to be associated with the deep subduction of cooler slabs, whose partially serpentinized interiors remain hydrated to great depths, reaching the mantle transition zone (5-7) with their carbon budget intact.…”
Section: Provenance Of the Heavy Ironmentioning
confidence: 91%